The Overview of the Incidence of Hypotension After Spinal Anesthesia Induction in Sectio Caesarea Patients During Intra Anesthesia at Juanda Kuningan Hospital West Java: English - Hidayatullah, Riki; Lintang Suryani, Roro; Dewi, Pramesti (Global Indonesia Health Care (GOICARE), 2023)
Purpose: This study aimed to identify the incidence of hypotension after spinal anesthesia induction in SC patients during intra-anesthesia based on Body Mass Index (BMI), age, and baseline systolic blood pressure at Juanda Kuningan Hospital. Methods: This study used a quantitative descriptive method with a cross sectional approach. The sample in this study were all SC patients with spinal anesthesia techniques who met the criteria. The sampling technique used was purposive sampling with the slovin formula resulting in 90 respondents. And data analysis using univariate analysis. Findings: The results showed that the majority of respondents who experienced mild hypotension with excessive BMI status were 50 respondents (58.8%), the majority of respondents who experienced mild hypotension with early adulthood were 52 respondents (61.2%) and the majority of respondents who experienced mild hypotension with initial systolic blood pressure were at initial systolic blood pressure <120 mmHg and 120-130 mmHg as many as 31 respondents (36.5%). Conclusions: The results of this study illustrate that the majority of respondents will experience hypotension after spinal anesthesia induction. This is because spinal anesthesia can block sympathetic nerves, resulting in a decrease in circulating arterial tone, this condition causes peripheral arterial vasodilation. This vasodilating effect can result in a decrease in vascular resistance (hypotension). For further researchers to be able to develop this study to look for other variables that may be associated with the incidence of hypotension after induction of spinal anesthesia in SC patients so that the results of the study will show more variation.